Do analysts underreact to pension underfunding? Evidence from forecast~bias and funding ratios of~DB~plans in Korea - Jung Hee Noh; Heejin Park (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2025)
This study aims to empirically investigate the relationship between the funding status of defined benefit (DB) pension plans and the forecast bias of financial analysts. While prior research has documented the impact of pension underfunding on firm performance, investment efficiency and firm value, relatively little attention has been paid to how this information is reflected in analysts' forecasts. This paper seeks to fill that gap by examining whether financial analysts systematically underreact to the risks associated with underfunded pension obligations. The study focuses on the pension funding ratio (PFR), defined as the difference between plan assets and projected benefit obligations (PBO), scaled by market capitalization. A lower PFR indicates greater underfunding. Using a comprehensive sample of listed firms in Korea from 2011 to 2022, during which consolidated financial statements under K-IFRS became mandatory, the analysis evaluates the sensitivity of analysts' forecasts to underfunding risks across performance categories. Forecast bias is measured across multiple dimensions, including sales, earnings, cash flow and capital expenditures. The central hypothesis is that analysts issue more optimistic performance forecasts for firms with lower PFRs due to the complexity of pension accounting and the limited transparency of related disclosures. Empirical evidence supports this hypothesis, showing that analysts systematically underreact to underfunding risks when forming forecasts. By highlighting the informational role of pension funding status in analyst forecasts, this study contributes to the literature on financial disclosure, information asymmetry and market efficiency. It also offers policy implications for improving pension-related transparency and guiding more informed forecasting practices in capital markets.
Keywords: 330; Information asymmetry; Financial analysts; Forecast bias; Defined benefit pension plan; Funding ratio